(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Ovarian tumors are the 7th most common cause of cancers in women worldwide. Despite advancements in both treatment and diagnosis, the morbidity and mortality associated with ovarian tumors continue to rise. In Bangladesh, 3132 cases were reported in 2015 and more cases are expected to be reported as diagnostic techniques continue to improve. Among ovarian tumors, dysgerminomas are one of the most common malignant ovarian neoplasms diagnosed in women under the age of 20. The following case study of a 12-yearold with abdominal pain and concomitant chest pain is an atypical presentation of dysgerminoma. This patient was diagnosed initially as having an ovarian neoplasm on the basis of a physical examination which was eventually corroborated by an ultrasound scan. Laparoscopic removal was eventually done as the patient was young and had desired a more cosmetically viable management protocol. At laparoscopy, the left ovary was found to be pearly white and enlarged, measuring 3.5x5.5 cm. It was removed and sent for histopathologic examination, which revealed that the patient had dysgerminoma. The patient remains in close follow up. JCMCTA 2019 ; 30 (2) : 99-101